ANALISIS KEPUASAN KUALITAS LAYANAN SISTEM INFORMASI AKADEMIK MENGGUNAKAN METODE TAM III - Anastasia Mude; Ferdinandus Lidang Witi (Jurnal Informatika, 2019)
This research aimed to comprehend the effect of variables external consisting of experience, subjective norm, perceptions, job relevance, output quality and result demonstrability, computer self efficacy, perceptions of external control, computer anxiety, computer playfulness, perceived enjoyment, and objective usability for perceived usefulness, perceived easy of use, service quality, behavioral intention, use behavior and user satisfaction of academic information system. The population of this students of AMIK Parna Raya Manado in academic year of 2013 and 2014. By using Slovin method, it was obtained the rate of the sample amount of 120 students. Data collection techniques using questionnaires and the model used Technology Acceptance Model (TAM III). It had been used Structural Equation Model (SEM) for examining the relation between those variables. The result of showed that the use TAM III method of significantly affected of the service quality satisfaction of academic information system. Keywords : Technology Acceptance Model, Structural Equation Model